The Time Course of Quadriceps Strength Recovery After Total Knee Arthroplasty Is Influenced by Body Mass Index, Sex, and Age of Patients: Systematic Review and Meta-Analysis - Paravlic, Armin H.; Meulenberg, Cécil J.; Drole, Kristina (Frontiers in Medicine, 2022)
Introduction For patients with osteoarthritis who have undergone total knee arthroplasty (TKA), quadriceps strength is a major determinant of general physical function regardless of the parameters adopted for functional assessment. Understanding the time course of quadriceps strength recovery and effectiveness of different rehabilitation protocols is a must. Therefore, the aim of this study was to: (i) determine the magnitude of maximal voluntary strength (MVS) loss and the time course of recovery of the quadriceps muscle following TKA, (ii) identify potential moderators of strength outcomes, and (iii) investigate whether different rehabilitation practices can moderate the strength outcomes following TKA, respectively. Design General scientific databases and relevant journals in the field of orthopedics were searched, identifying prospective studies that investigated quadriceps’ MVS pre-to post-surgery. Results Seventeen studies with a total of 832 patients (39% males) were included. Results showed that in the early post-operative days, the involved quadriceps’ MVS markedly declined, after which it slowly recovered over time in a linear fashion. Thus, the greatest decline of the MVS was observed 3 days after TKA. When compared to pre-operative values, the MVS was still significantly lower 3 months after TKA and did not fully recover up to 6 months following TKA. Furthermore, a meta-regression analysis identified that the variables, time point of evaluation, patient age, sex, and BMI, significantly moderate the MVS of the quadriceps muscle. Conclusion The analyzed literature data showed that the decrease in strength of the involved quadriceps muscles following TKA is considerable and lasts for several months post-surgery. Therefore, we recommend to specifically target the strengthening of knee extensor muscles, preserve motor control, and apply appropriate nutrition to ensure a holistic quadriceps muscle recovery. Since age, sex, and BMI were found to be moderating factors in patients’ recovery, further research should include specific analyses considering these moderators.